Tuning molecular motor transport through cytoskeletal filament network organization. Issue 8 (4th February 2020) - Scholz, Monika; Weirich, Kimberly L.; Gardel, Margaret L.; Dinner, Aaron R.
Abstract : Myosin II motor dynamics have signatures that report on the structure of the underlying network of crosslinked cytoskeletal filaments. Abstract : Within cells, crosslinking proteins organize cytoskeletal filaments both temporally and spatially to create dynamic and structurally diverse networks. Molecular motors move on these networks for both force generation and transport processes. How the transport statistics depend on the network architecture remains poorly characterized. Using cross-linking proteins (α-actinin, fimbrin, fascin, or filamin) and purified actin, we create cytoskeletal networks with diverse microscopic architectures. We track the motion of myosin II motor proteins moving on these networks and calculate transport statistics. We observe that motor dynamics change predictably based on the bundling of filaments within the underlying networks and discuss implications for network function.